Retrospective Study Regarding the Correlation between Dental Anxiety and Color Preferences in Children with Severe Early Childhood Caries - Daniela Esian; Cristina Bica; Alexandru Vlasa; Eugen Bud; Elena Stepco; Anamaria Bud; Liana Beresescu (MDPI AG, 2024)
Background: Severe early childhood caries (S-ECC) is recognized as a significant chronic disease which affects the quality of life starting at very young ages and has a very rapid evolution towards pulp complication and loss of dental tissue. Children with a high caries index DMFT are more likely to develop high levels of dental anxiety, which will influence the degree of cooperation during dental procedures. Emotions play an important role in the psychosomatic development of children, and all the factors that contribute to the modeling of these emotional states must be known and taken into consideration. Aim: The aim of this study was to assess the association between dental anxiety in children with S-ECC and the color preferences for the components of the dental environment to reduce the levels of dental anxiety during medical visits. Material and Method: For this study, 91 children between 3 and 6 years of age diagnosed with S-ECC were selected from the Pediatric Dentistry Department of UMFST from Targu Mures and from a private dental office. The level of dental anxiety was determined by measuring the pulse rate, and a questionnaire was completed to establish the color preferences for the dental office environment and the dentist's attire. For this purpose, six different colors and their variants with three shades less intensity were chosen by using RGB (Red, Green, and Blue) identification codes for each color. Result: The results showed that there was a statistically significant difference between the age of the subjects and dental anxiety levels, but there was no significant correlation between the DMFT score and dental anxiety. Also, the results showed that there was no significant difference between girls and boys when choosing the colors preferred by them for the dental office, but when comparing the colors that represented happiness, significant statistical difference was found between the girls' and boys' groups (p = 0.0039). For all the subjects, the colors associated with happiness were light yellow and pink, while the colors associated with anxiety were red and dark blue. Conclusion: The data obtained showed that dental anxiety is strongly influenced by age, and an important role in inducing positive emotions is played by the dental environment if dressed in specific colors in order to reduce dental anxiety and create familiar conditions, especially for young children with S-ECC.